Exploding Foil Initiator (EFI) Modes of Operation Determined Using Down‐Barrel Flyer Layer Velocity Measurement. Issue 3 (24th October 2016) - Borman, Alexander J.; Dowding, Colin F.; Griffiths, Jonathan D.; Seddon, Dick
Abstract: Exploding Foil Initiator (EFI) flyer layer velocities measured down the barrel of an EFI are presented. Flyer velocity was shown to be proportional to supply voltage and of a similar order to other studies previously conducted. Bridge volume ejection was shown to be proportional to capacitor voltage. Current density increased with respect to capacitor voltage up to a point of saturation between 2400 V and 3000 V (evidenced electrically). Beyond the saturation voltage, high voltages demonstrated sustained energy delivery at a reduced current. This work indicates that control of active bridge volume or electrical supply signal may enable more closely controlled EFI flyer layer ejection behavior, and it demonstrates the relevance of using current per active bridge (specific current) as a metric to describe EFI electrical performance with relevance to dynamic response of the EFI. The impulse delivered by an EFI can be modulated via manipulation of the firing circuit input signal giving rise to system behavior variation. Abstract :